INFLUENCIA DE LA PANDEMIA POR EL SARS-CoV-2 EN LA VARIACIÓN TEMPORAL DEL PM2.5 EN LAS CIUDADES DE LIMA METROPOLITANA Y AREQUIPA - Garcia-Sierra, Antonio Benjamin (2025)
The SARS-CoV-2 pandemic involved a set of restriction measures in order to guarantee social distancing. Consequently, these measures altered the environmental conditions in the areas where they were applied. The temporal variation of particulate matter of 2.5 microns in diameter or less (PM2.5) concentrations was evaluated in two cities by this study: Metropolitan Lima and Arequipa in the years 2019 – 2021. To carry it out, PM2.5 concentrations data from the National Service of Meteorology and Hidrology (SENAMHI by its acronym in Spanish) for Metropolitan Lima city and PM2.5 concentrations data from the Regional Directorate of Environmental Health (DIRESA by its acronym in Spanish) of Arequipa for Arequipa city were used. The results showed that in general the concentrations of PM2.5 decreased in the year 2020 because of the social distancing measures adopted by the government and increased in the year 2021 due to the easing of restrictive measures.